Elastin-Like Recombinamers As Smart Drug Delivery Systems - Arias, F Javier; Santos, Mercedes; Ibanez-Fonseca, Arturo ; 0000-0002-2223-5041; Pina, Maria Jesus; Serrano, Sofía (Current drug targets, 2018)
BACKGROUND: Drug delivery systems that are able to control the release of bioactive molecules and designed to carry drugs to target sites are of particular interest for tissue therapy. Moreover, systems comprising materials that can respond to environmental stimuli and promote self-assembly and higher order supramolecular organization are especially useful in the biomedical field. Objetive: This review focuses on biomaterials suitable for this purpose and that include elastin-like recombinamers (ELRs), a class of proteinaceous polymers bioinspired by natural elastin, designed using recombinant technologies. The self-assembly and thermoresponsive behaviour of these systems, along with their biodegradability, biocompatibility and well-defined composition as a result of their tailormade design, make them particularly attractive for controlled drug delivery. RESULTS: ELR-based delivery systems that allow targeted delivery are reviewed, especially ELR-drug recombinant fusion constructs, ELR-drug systems chemically bioconjugated in their monomeric and soluble forms, and drug encapsulation by nanoparticle-forming ELRs. Subsequently, the review focuses on those drug carriers in which smart release is triggered by pH or temperature with a particular focus on cancer treatments. Systems for controlled drug release based on depots and hydrogels that act as both a support and reservoir in which drugs can be stored will be described, and their applications in drug delivery discussed. Finally, smart drug-delivery systems not based on ELRs, including those comprising proteins, synthetic polymers and non-polymeric systems, will also be briefly discussed. CONCLUSION: Several different constructions based on ELRs are potential candidates for controlled drug delivery to be applied in advanced biomedical treatments.
Copyright© Bentham Science Publishers; For any queries, please email at epub@benthamscience.org.
Keywords: Biocompatible Materials/chemistry; Drug Carriers/chemistry; Drug Delivery Systems/methods; Elastin/chemistry; Humans; Nanoparticles/chemistry; Polymers/chemistry